Imaging Evaluation of Disorders of Sex Development - Eapen, Anu; Chandramohan, Anuradha; Simon, Betty; Putta, Tharani; John, Reetu; Kekre, Aruna (Journal of Gastrointestinal and Abdominal Radiology, 2020)
Disorders of sex development (DSD) refer to congenital conditions with a typical development of chromosomal, gonadal, or anatomic sex. In the revised classification of DSD, there are three categories based on karyotype: 46,XX DSD; 46,XY DSD; and sex chromosome DSD. Imaging, as part of a multidisciplinary approach to management of DSD, has a key role in gender assignment. The main role of imaging is to help in identifying the gonads and the Müllerian structures. Ultrasound is useful, especially in the neonate with ambiguous genitalia. Magnetic resonance imaging is a useful modality to locate and characterize the gonads in young girls with primary amenorrhea and also to identify streak gonads, which have a risk of malignancy.
Keywords: disorders of sex development; DSD; imaging; ambiguous genitalia; gonads